Characterization of nanoporous structures: from three dimensions to two dimensions. Issue 40 (4th October 2016) - Zhao, Cang; Qiao, Yu
Abstract : The SEM-image polishing based QSIA technique may pave the road to fast and accurate data mining of nanoporous structures. Abstract : The scanning electron microscope (SEM) has revealed a colorful three-dimensional world due to its great depth of field. However, the abundance of structural information imposes tough challenges to quantitative image analysis. In the current investigation, we developed a SEM-image polishing (SIP) based quantitative SEM-image analysis (QSIA) technique. As an example, QSIA was employed to characterize nanoporous silica. The results confirmed that the nanoporous silica samples, processed via sol–gel methods, were single-parameter, with the pore size being the only variable. The QSIA technique may pave the way to fast and accurate data mining of nanoscaled materials.